2004
DOI: 10.1677/joe.0.1820325
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cell proliferation and regulation of estrogen receptor alpha signaling pathway by arsenic trioxide on human breast cancer MCF-7 cells

Abstract: In recent years, breast cancers have aroused much concern. Together with a growing incidence all over the world, the development of drug resistance to tamoxifen, the most commonly prescribed chemotherapeutic drug for breast cancer patients, has highlighted the importance of developing a new chemotherapeutic drug in combating breast cancer. With the aim of treating breast cancers, the anti-tumor effects of arsenic trioxide in MCF-7 cells have been studied.MCF-7 cells are estrogen responsive cells which mimic br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…However, our current results demonstrate clearly that treatment with As alone does not significantly alter the level of GR either for cells expressing endogenous GR (H4IIE) or those expressing stably integrated GR (10.1.13.14, Fig 2). In contrast, it has been reported that As decreased cellular ER levels after ≥24 hrs of treatment (39,45,46). While those ER changes might eventually lead to alterations in the response of ER-mediated gene expression to As, it is unlikely that such long-term changes would significantly alter gene expression under short term treatment conditions (i.e., up to 18-24 hr after As treatment).…”
Section: Discussionmentioning
confidence: 89%
“…However, our current results demonstrate clearly that treatment with As alone does not significantly alter the level of GR either for cells expressing endogenous GR (H4IIE) or those expressing stably integrated GR (10.1.13.14, Fig 2). In contrast, it has been reported that As decreased cellular ER levels after ≥24 hrs of treatment (39,45,46). While those ER changes might eventually lead to alterations in the response of ER-mediated gene expression to As, it is unlikely that such long-term changes would significantly alter gene expression under short term treatment conditions (i.e., up to 18-24 hr after As treatment).…”
Section: Discussionmentioning
confidence: 89%
“…We speculate that low arsenic concentrations might have a stronger effect on female progenitors, acting through the up-modulation of oncogenes, such as ras, myc, or hTERT mRNA and protein expression, and probably also by interfering with the expression of estrogens receptor (ERs) as already observed (Davey et al, 2007). In our previous study we reported that arsenic was able to interfere with ERs expression in murine bone marrow cells (Cimino-Reale et al, 2008), whereas other studies showed that arsenic can modulate basal expression of steroid receptors (Stoica et al, 2000;Chen et al, 2002;Chow et al, 2004). Liu et al (2007) demonstrated that transplacental exposure to arsenic in mice significantly alters the expression of various genes encoding for estrogens signalling and steroid synthesis.…”
Section: Discussionmentioning
confidence: 91%
“…Chow et al demonstrated that As 2 O 3 inhibited estradiol (E2)-induced cell proliferation at low concentrations (0.25-1 mM) and stimulated apoptosis at higher concentrations (2 mM) in the MCF-7 breast cancer cell line. 19 In contrast, others have shown that As 2 O 3 (1 mM) stimulated E2-induced proliferation of the MCF-7 cell line and that addition of an antiestrogen blocked this effect. 21 It is unclear to why there is discrepancy in results, although there is some suggestion of a concentration-dependent effect.…”
Section: Discussionmentioning
confidence: 92%
“…18 Arsenic trioxide has also been shown to suppress the action of estrogen through regulation of estrogen receptor-alpha (ER-a) expression in breast cancer cell lines. [19][20][21] Endometrial cancer is the fourth most common cancer in women in the United States and has been increasing in frequency due to an aging population and changes in dietary and hormonal factors. It is estimated that 40 000 new cases will be diagnosed in 2007, and 7400 women will succumb to this disease.…”
Section: Introductionmentioning
confidence: 99%